The concept of two-dimensional electrophoresis-guided purification proven by isolation of rhodocetin from calloselasma rhodostoma (Malayan pit viper) - Tang, M.S.; Vejayan, J.; Ibrahim, H. (BMC, 2011)
Two-dimensional gel electrophoresis (2DE) is an important tool for investigating the complexity of snake venom proteomes. Apart from applications based on whole proteome analysis, we suggest that 2DE can be used as an assay to guide the progress of protein purification. The aim of this study was to prove the feasibility of this concept by using it to purify rhodocetin from Calloselasma rhodostoma venom. Rhodocetin (α subunit) spot on the 2DE profile of C. rhodostoma venom was first identified and confirmed by mass spectrometry, with a molecular mass of 16 kDa and calculated pI of 5.16. Rhodocetin was subsequently purified by successive anion-exchange and gel filtration chromatography. Every peak from both chromatography profiles was collected and tested on 2DE. The presence of rhodocetin (α subunit) spot in the 2DE profile of the peak DP2 indicated the presence of the protein. The purified compound was used to spike the crude venom. A spiked spot with a 1.6-fold increase in intensity was observed and its position matched to that of rhodocetin (α subunit) on the 2DE profile. Together, these spots confirmed the identity of the purified compound as rhodocetin. Hence, our results have demonstrated the effectiveness of the concept we now term 2DE-guided purification.